Metamorphic Fasies of Metamorphic Rocks in the Mekongga Complex, Loea Region, East Kolaka Regency, Southeast Sulawesi Province - Sugiono; Hasria; S. Asfar; L. O. Ngkoimani; Muliddin (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2026)
Metamorphic rocks in the study area are part of the Mekongga Metamorphic Complex which is Carbon age. It was interpreted as part of the Malihan complex in southeast sulawesi arm. Administratively located in the area of Loea, Kolaka Timur district, Southeast Sulawesi. Geographically located in coordinates 121°53'0